Main life history traits of the largehead hairtail, Trichiurus lepturus (Linnaeus, 1758) from the Senegalese North coast - Diop Khady; Diouf Khady; Ndiour Yacine; Diouf Sidya; Jouffre Didier (Fisheries & Aquatic Life)
Trichiurus lepturus is a benthopelagic species of socio-economic importance in Senegal. Despite its intensive exploitation, there is a lack of studies on its life traits in West African waters, particularly in Senegal. This study aims to determine the biological parameters of this species in the northern coastal zone of Senegal. Samples were collected monthly from April 2015 to March 2016 in Cayar, one of the main landing sites in Senegal. A total of 354 specimens were caught with longlines. Condition factor varied between the years with a peak in May. Positive allometric growth (b = 3.24) was found for this species. The reproductive period mainly occurred from April to July, and the sizes at first sexual maturity were 831 mm and 766 mm for females and males, respectively. Absolute fecundity was highly variable (39,976.88 ± 19,793.02 oocytes). The growth parameters estimated were asymptotic length (L∞) = 134 cm and the growth coefficient (K) = 0.0016. The maximum observed age was 1 year and 7 months. These parameters could be integrated into stock assessment models, providing a better estimate of the exploitation level of this resource and aiding in the formulation of more scientifically informed management measures for sustainable exploitation.